Transcriptional profiles of Microcystis reveal gene expression shifts that promote bloom persistence in in situ mesocosms - Lauren E. Krausfeldt; Paisley S. Samuel; Robert P. Smith; Hidetoshi Urakawa; Barry H. Rosen; Rita R. Colwell; Jose V. Lopez (Microbiology Spectrum)
ABSTRACT Harmful algal blooms caused by cyanobacteria threaten aquatic ecosystems, the economy, and human health. Previous work has tried to identify the mechanisms that allow blooms to form, focusing on the role of nutrients. However, little is known about how introduced nutrients influence gene expression in situ. To address this knowledge gap, we used in situ mesocosms initiated with water experiencing a Microcystis bloom. We added pulses of nutrients that are commonly associated with anthropogenic sources to the mesocosms for 72 hours and collected samples for metatranscriptomics to examine how the physiological function of Microcystis and bloom status changed. The addition of nitrogen (N) as urea, but not the addition of PO4, resulted in conspicuous bloom persistence for at least 9 days after the final introduction of nutrients. The addition of urea initially resulted in the upregulation of photosynthesis machinery, as well as phosphate, carbon, and N transport and metabolism. Once Microcystis presumably became N-replete, upregulation of amino acid metabolism, microcystin biosynthesis, and other processes associated with biomass generation occurred. These capacities coincided with the upregulation of toxin-antitoxin systems, CRISPR-cas genes, and transposases suggesting that phage defense and genome rearrangement are critical in bloom persistence. Overall, our results show the stepwise transcriptional response of a Microcystis bloom to the introduction of nutrients, specifically urea, as it is sustained in a natural setting. The transcriptomic shifts observed herein may serve as markers of the longevity of blooms while providing insight into why Microcystis blooms over other cyanobacteria.IMPORTANCEHarmful algal blooms represent a threat to human health and ecosystems. Understanding why blooms persist may help us develop warning indicators of bloom persistence and create novel mitigation strategies. Using mesocosm experiments initiated with water with an active bloom, we measured the stepwise transcription changes of the toxin-producing cyanobacterium Microcystis in response to the addition of nutrients that are important in causing blooms. We found that nitrogen (N), but not phosphorus, promoted bloom longevity. The initial introduction of N resulted in the upregulation of genes involved in photosynthesis and N import. At later times in the bloom, upregulation of genes involved in biomass generation, phage protection, genomic rearrangement, and toxin production was observed. Our results suggest that Microcystis first fulfills nutritional requirements before investing energy in pathways associated with growth and protection against competitors, which allowed bloom persistence more than a week after the final addition of nutrients.